Sustainable Entrepreneurship among Small and Medium Enterprises(SMEs) in Malaysia - KOE, WEI LOON; Abdul Majid, Izaidin (2013)

(untitled)
Sustainable entrepreneurship has brought many changes to the business world. Among them, businesses nowadays are required to integrate sustainability management into their business activities. Although sustainable entrepreneurship has been regarded as a vital concept in rectifying environmental and social problems through entrepreneurial activities, there remain scant studies. This preliminary study was geared towards examining the extent of sustainable practices among small and medium enterprises (SMEs) of various characteristics in Malaysia. The descriptive analyses revealed that SMEs were quite positive towards sustainable practices in which more than half of the SMEs were having plans for it. However, the actual embarkation on sustainability among SMEs was less embracing. It also found that female business owners were slightly keener to sustainable management than males. In addition, manufacturing firms, corporations, small-size enterprises and firms with five to ten years of history were more prompted to exercise sustainable practices than the others. As such, more efforts are definitely needed from various parties to promote sustainable entrepreneurship among SMEs to ensure equal economic, social and environmental gains.